Utilization and Impact of Career Services Among Collegiate Athletes - Evan Davis; Shea Brgoch; Leeann Lower-Hoppe; Makena Lynch; Duncan Johnston; Daniel Wray; Kristy McCray; Megan Parietti (Bowling Green State University, 2022)
Career readiness is a concern within the American educational system, particularly among student-athletes that must manage intense time commitments both on and off the field. Student services have emerged in higher education to support career preparation, but the utilization and impact of these services for collegiate athletes is largely unknown. The systems-theory framework (STF) of career development identifies a multitude of internal and external factors that influence individual career development. Guided by STF, the purpose of this study was to predict the factors that influence collegiate athletes' utilization of career services and resulting perceived career skills. An online questionnaire was distributed to collegiate athletes at a Division I university, resulting in 143 collegiate athletes completing the questionnaire. Multiple regression analysis demonstrated collegiate athletes' familiarity with career services significantly predicted their utilization of career services. In turn, utilization of only four of nine career services investigated (i.e., Careers Online, Career Fairs, Career Workshops, and Athletic Academic Advisor) significantly predicted perceived career skills positively. Implications for the design and marketing of career services for collegiate athletes are discussed.